Causes and Impact of Cryopreservation-Associated Damage on Different Parameters of Human Spermatozoa and its Clinical Impact - Andrea Palomar Rios; Inmaculada Molina Botella (European Medical Journal, 2019)
Sperm cryopreservation has been widely used for assisted reproductive technology (ART). Indications for sperm cryopreservation include donor insemination, cryopreservation prior to surgical infertility treatment, and malignancies to avoid additional surgery in couples undergoing repeated in vitro fertilisation (IVF) or intracytoplasmic sperm injection (ICSI) cycles. However, dramatic changes during cryopreservation have detrimental effects on the sperm membrane, resulting in a large increase in the percentage of poorly motile sperm or sperm with abnormal morphology. The negative effects related to rapid temperature decrease, such as osmotic injury, cellular dehydration, intracellular ice crystal formation, and oxidative stress can also damage the sperm in ways that affect reproductive outcome. This comprehensive review focusses on describing the detrimental effects of the cryopreservation process on sperm and aims to clarify that not all impaired sperm parameters have the same impact on the clinical practice of ART. Regarding the parameters studied, some of the biomarkers used for sperm maturity, hyaluronic acid binding capacity, or damaged DNA have limited clinical significance compared to other semen parameters which provide more useful information for clinical practice and are often dismissed, such as total motility or total motile sperm count (TMSC). In the authors' experience, TMSC gives valuable quantitative information about the number of viable spermatozoa. Indeed, TMSC should be assessed specifically for groups of patients in which sample availability is limited.